Dynamics of temporal foraging and feeding index of Labeo rohita (Hamilton, 1822) in East Kolkata wetlands, a Ramsar site - Kumar, Avinash; Das, Sudhir Kumar; Bhakta, Dibakar (Journal of the Inland Fisheries Society of India, 2020)
Temporal variations in the foraging and feeding index of Labeo rohita collected from East Kolkata wetlands were studied for one year. The gut content analysis was carried out on 232 fish samples of size ranging between 149 mm and 331 mm in total length. The observations indicated that the fish diet comprisedof 19.2% Chlorophyceae, 10.2% Cyanophyceae, 10.4% Bacillariophyceae, 7.7% flagellates, 2.7% macro-vegetation, 9.2% rotifers, 4.9% copepods, 6.3%cladocerans, 7.2% protozoans, 11.8% decayed organic matter, 7.5% sand and mud and 0.8% miscellaneous items. The feeding indices varied in different months and were relatively higher during August and September and lower during June and July. The forage ratio indicated a preference towards phytoplanktons (Chlorophyceae, Cyanophyceae, and Bacillariophyceae)in large size fish and preference of zooplanktons in small size fish.Key words Labeo rohita; Food and feeding habits; Forage ratio; Phytoplankton; Zooplankton